Training, soft skills and productivity: Evidence from a field experiment in retail - María F. Prada; Graciana Rucci; Sergio Urzua (Inter-American Development Bank (IDB), 2019)
Understanding the causal association between skills and productivity is essential for designing effective training programs. This paper evaluates an intervention aimed at boosting leadership and communication skills among store managers and sales associates from a large Latin American retailer. The empirical analysis is carried out using longitudinal information gathered by the firm and through two skills surveys. The Identification exploits the experimental design in the context of a difference-in-difference strategy. The results indicate large positive effects of the training program on store-level productivity. We further link these Findings to individual-level performance measures. In particular, we document positive effects on total sales and numbers of transactions for all workers. Regarding the mechanisms, we provide evidence suggesting that the intervention was more effective in boosting leadership skills than communication skills. Spillovers from trained managers to untrained sales representatives also contribute to the main effects. Our findings point towards the possibility of increasing productivity through training programs targeting critical skills.
Keywords: C93; J24; M53; O15; 330; Socio-emotional skills; training; productivity; experiments with firms